PENGARUH PENGUASAAN SOFT SKILL TERHADAP KESIAPAN CALON TENAGA KERJA DALAM MEMASUKI DUNIA KERJA PADA PROGRAM PELATIHAN MENJAHIT DI UPTD LATIHAN KERJA DINAS KOPERASI TENAGA KERJA DAN TRANSMIGRASI PROVINSI NTT - Kalla, Ekanita Herlinda Sandy; Simbolon, Gallex; Neonufa, Samrid (Universitas Nusa Cendana, 2024)
ABSTRACT This study aims to determine the effect of Soft Skills on Work Readiness in the Sewing Training Program at the UPTD Work Training Department of Manpower Cooperatives and Transmigration of NTT Province partially. The type of research used in this research is quantitative associative. The population in this study were sewing training participants by determining the sample using the Slovin formula. The research data used are primary data obtained through the distribution of questionnaires to 44 research respondents using cluster sampling technique. The data analysis technique used is simple linear regression analysis which is then processed, analyzed and discussed to answer the problems in this study. The results of the study using the t test or partial, soft skills have a significant effect on job readiness with a significant value of 0.5244 > 0.2973. The magnitude of the influence of soft skills on the work readiness of learning residents in the sewing training program is 68.731 which means that the percentage contribution of the soft skill variable to work readiness is 69%. Keywords: Soft Skill, Work Readiness, BLK